PERCEPTION OF LUXURY VALUE, HEDONISTIC LIFESTYLE, INCOME INFLUENCE DECISIONS TO PURCHASE BRANDED GOODS - Baiq Dinna Widiyasti; Raden Bagus Faizal Irany Sidharta (Jurnal Manajemen dan Bisnis Performa, 2025)
Branded goods are synonymous with expensive prices, used by people with high income levels and have a luxurious lifestyle. Mataram City, which is known to have a per capita income of Rp. 1,010,000 in 2024. It turns out to have a market potential for branded goods. This can be seen from the users, as well as branches and outlets opened by well-known branded goods manufacturers. The purpose of this study was to determine the Perception of Luxury Value, Hedonism Lifestyle and Income influence on Branded Goods Purchasing Decisions in Mataram City. The study was conducted using an associative quantitative approach with a sample of 137 branded goods users. Analyzed using the validity test method, reliability, classical assumptions as well as descriptive and verification tests, using SPSS 27, it was found that Perception of Luxury Value and Hedonism Lifestyle have a significant influence on Branded Goods Purchasing Decisions in Mataram City, but purchasing decisions are not significantly influenced by income. This research is expected to be able to provide a special study as a consideration regarding the characteristics of products or consumer lifestyles in determining special marketing strategies for local and national branded goods producers to be able to be competitive.